Green Future in Hospitality: Sustainability and Innovation - Nagy, Zoltán; Kovács, Tibor; Misik, Tamás (Acta Carolus Robertus, 2025)
Sustainability has become a key factor in modern hospitality, as consumers increasingly prefer restaurants that implement environmentally friendly solutions. Practices such as sourcing ingredients from local producers, using seasonal ingredients, minimizing food waste, and adopting alternative packaging solutions not only promote sustainability but also enhance a restaurant's economic competitiveness. The application of the nose-to-tail and stem-to-root concepts reduces ingredient waste, while food waste management initiatives like Munch or composting provide further sustainable alternatives.Sustainability strategies in hospitality significantly influence consumer decision-making. Research shows that a large proportion of guests expect restaurants to take environmentally conscious measures, making sustainability an essential part of restaurant operations and marketing. Developing seasonal menus, collaborating with local producers, and implementing energy-efficient solutions are becoming increasingly popular.Sustainable hospitality not only protects the environment but also contributes to economic and community development. The adoption of sustainable strategies ensures long-term benefits for the restaurant sector while meeting modern consumer demands.
Keywords: sustainability; hospitality; food waste reduction; seasonal menu; local producers; eco-conscious hospitality